2002
DOI: 10.1029/2001ja009217
|View full text |Cite
|
Sign up to set email alerts
|

Heliospheric magnetic field strength and polarity from 1 to 81 AU during the ascending phase of solar cycle 23

Abstract: [1] The Voyager 1 (V1) observations of the heliospheric magnetic field strength B agree with Parker's model of the global heliospheric magnetic field from 1 to 81.0 AU and from 1978 to 2001.34 when one considers the solar cycle variations in the source magnetic field strength and the latitude/time variation in the solar wind speed. In particular, Parker's model, without adjustable parameters, describes the general tendency for B to decrease with increasing distance R from the Sun, the three broad increases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 67 publications
5
49
0
Order By: Relevance
“…At some locations it extends up to 30 • from the HCS, which explains the observations of slow wind at high latitudes. The HCS is not always symmetrically located inside the S-Web but can lie near one edge and, in fact, the HCS is often observed in the heliosphere to occur close to one of the slow wind boundaries rather than symmetrically between them (Burlaga et al 2002). Although the Q layers are densely spaced, they are not space filling, so we expect that the wind in the S-Web region will actually consist of a mixture of slow and fast, as observed.…”
Section: The S-web Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…At some locations it extends up to 30 • from the HCS, which explains the observations of slow wind at high latitudes. The HCS is not always symmetrically located inside the S-Web but can lie near one edge and, in fact, the HCS is often observed in the heliosphere to occur close to one of the slow wind boundaries rather than symmetrically between them (Burlaga et al 2002). Although the Q layers are densely spaced, they are not space filling, so we expect that the wind in the S-Web region will actually consist of a mixture of slow and fast, as observed.…”
Section: The S-web Modelmentioning
confidence: 97%
“…2. The HCS appears as the dark red line and the contours of high Q as white, (adapted from Antiochos et al 2011) observed photospheric flux distribution, but less structured than in Fig. 2, and two "magnetic carpet" bipoles.…”
Section: The S-web Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow wind is found at low latitudes and surrounds the HCS (heliospheric current sheet) (Burlaga et al 2002). The HCS is always observed to be embedded in slow wind, which is sometimes observed to extend as much as 30 or more from the HCS.…”
Section: Fast and Slow Solar Windmentioning
confidence: 99%
“…1. At solar minimum, the magnetic field is dipolar and the average solar wind magnetic field magnitude at 1 AU is small (Burlaga et al, 2002 streamer belt and current sheet are near the equator and are a source of low-speed, 400 km/s solar wind (see Gazis, 1996). Few interplanetary coronal mass ejections (ICMEs) occur near solar minimum, so few shocks form (see Cane and Richardson, 2003), and the average helium abundance (averaged over all solar wind conditions) is low, 1-2% (Aellig et al, 2001).…”
Section: Solar Cycle Dependence Of the Solar Windmentioning
confidence: 99%